2002
DOI: 10.1002/1521-3773(20021202)41:23<4463::aid-anie4463>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Facile Assembly of Cell Surface Oligosaccharide Mimics by Copolymerization of Carbohydrate Modules

Abstract: Artificial glycoconjugate polymers (glycopolymers) and other multivalent carbohydrate ligands constitute a new class of biomimetic supramolecules. [1] They have shown many biological applications in, for example, cultivation, tumor diagnosis and detection, and the trapping of viruses and bacterial toxins. [2] Their utility is ascribed mainly to their strong and species-specific interactions with the receptor proteins as a result of multivalent binding and/or carbohydrate cluster effects. Although most of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The second step of the synthesis, the coupling between 1a and b and acryloyl chloride, was also conducted in aqueous solution without isolating 1a and b . The amino group selectively reacted with acryloyl chloride in aqueous solution because the nucleophilicity of amino group was higher than those of hydroxy group and water . After the first step reaction, the reaction mixture was washed with chloroform to thoroughly extract excess 4‐aminobenzentiol and was directly added with acryloyl chloride to yield 2a and b (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The second step of the synthesis, the coupling between 1a and b and acryloyl chloride, was also conducted in aqueous solution without isolating 1a and b . The amino group selectively reacted with acryloyl chloride in aqueous solution because the nucleophilicity of amino group was higher than those of hydroxy group and water . After the first step reaction, the reaction mixture was washed with chloroform to thoroughly extract excess 4‐aminobenzentiol and was directly added with acryloyl chloride to yield 2a and b (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…49 The utility of the carbohydrate module method as a tool to assemble oligosaccharide mimics of high biological significance was further supported by the development of new heteroglycopolymers that combined aFuc, 3-sulfo-b-Gal and 6-sulfo-b-GlcNAc exhibiting a significant increase in binding affinity and selectivity towards L-selectin. 50 The same concept was applied to the synthesis of galactotrehalose (GT) acrylamide polymers. The binding abilities of such polymers were evaluated against BSI-B 4 lectin (Bandeiraea simplicifolia), which is specific to a-galactoside-carrying oligosaccharides including Gb3 ceramide and human blood B determinants.…”
Section: (A) Heteroglycopolymersmentioning
confidence: 99%
“…The synthesis of the latter is seriously restricted by the difficulty in preparing the oligosaccharide in sufficient amount. Sasaki et al [95] found that acrylamide copolymers carrying only a-L-fucoside and 3-sulfo-b-D-galactoside residues showed strong activity in Scheme 27: Reagents and conditions: a) CF 3 COOH, n x CH 2 5 5CHOiC 4 H 9 , EtAlCl 2 , 1,4dioxane, 08C; b) i. NH 2 -NH 2 H 2 O, 1,4-dioxane, 608C, 4 h; ii. Ac 2 O, MeOH, rt, 1.5 h, 65%.…”
Section: Polymers With Glycidic Appendagesmentioning
confidence: 99%